Therapeutic Strategies in the Management of Nonresorbable Membrane and Titanium Mesh Exposures Following Alveolar Bone Augmentation: A Systematic Scoping Review - Poli, Pier Paolo; Beretta, Mario; Maiorana, Carlo; Souza, Francisley Ávila [UNESP]; Bovio, Andrea; Manfredini, Mattia (Quintessence Publishing, 2022)
Purpose: The exposure of nonresorbable membranes following alveolar bone augmentation is one of the most frequently occurring complications. This review aimed to investigate the treatments that can be adopted to manage the exposure of polytetraﬂuoroethylene-based membranes (PTFE-ms) and titanium meshes (TMs) and their outcomes. Materials and Methods: Two independent reviewers electronically and manually searched the EMBASE, PubMed/MEDLINE, Scopus, and Cochrane bibliographic databases to retrieve pertinent articles available between January 2000 and March 2021. Only human studies describing the type of treatment and the soft tissue outcome following exposure of PTFE-ms or TMs were included. Results: Overall, 11 articles in the PTFE-ms group and 24 in the TM group were included for data analysis. Results indicated that, in both groups, two distinct therapeutic strategies are mostly applied in case of exposure, namely, pharmacologic and mechanical treatments. Other options have been identiﬁed seldomly. Statistically signiﬁcant evidence of an association between the type of barrier membrane and the exposure rate (28.7% vs 38.5% for TMs and PTFE-ms, respectively; P =.019) and between the type of exposed device and the treatment outcome in terms of removal rate following therapy (11.9% and 44.4% for TMs and PTFE-ms, respectively; P <.001) was noted. Conclusion: In both groups, chlorhexidine applications and meticulous plaque control may lead to improved healing conditions after exposure. Surgical removal of the exposed portion can be considered to promote secondary intention healing. The beneﬁcial effects of systemic antibiotics could not be demonstrated in the management of the exposure but should be evaluated in case of graft infection.
Keywords: Barrier membranes; Bone regeneration; Complications; Dental implants; Titanium mesh